HaCRT1 of Heterodera avenae Is Required for the Pathogenicity of the Cereal Cyst Nematode - Liu, Jing; Peng, Huan; Su, Wen; Liu, Maoyan; Huang, Wenkun; Dai, Liangying; Peng, Deliang (Frontiers in Plant Science, 2020)
Cereal cyst nematodes (CCN) are sedentary biotrophic endoparasites that secrete effector proteins into plant tissues to transit normal cells into specialized feeding sites and suppress plant defenses. To understand the function of nematode effectors in Heterodera avenae, here we identified a calreticulin protein HaCRT1, which could suppress the cell death induced by Bax when expressed in N. benthamiana. HaCRT1 is synthetized in the subventral gland cells of pre-parasitic second-stage nematodes. Real-time PCR assays indicated the expression of HaCRT1 was highest in parasitic second-stage juveniles. Expression of an HaCRT1-RFP fusion in N. benthamiana revealed that it was localized in the Endoplasmic reticulum (ER) of the plant cell. The ability of H. avenae infecting plants was significantly reduced when HaCRT1 was knocked down by RNA interference in vitro. Arabidopsis thaliana plants expressing HaCRT1 were more susceptible than wild-type plants to P. syringae. The induction of defense related genes PAD4, WRKY33, FRK1 and WRKY29 after treatment with ﬂg22 was suppressed in HaCRT1-transgenic plants. Also, the ROS accumulation induced by ﬂg22 was reduced in the HaCRT1-transgenic plants compared to wild-type plants. HaCRT1 over-expression increased the cytosolic Ca2+ concentration in A. thaliana. These data suggested that HaCRT1 may contribute to the pathogenicity of H. avenae by suppressing host basal defense.